A Review On: Recent Advancement of Stomach Specific Floating Drug Delivery System - Shruti, Shukla (International Journal of Pharmaceutical & Biological Archive, 2012)
The purpose of writing this review on floating drug delivery systems (FDDS) was to compile the recent literature with special focus on the principal mechanism of floatation to achieve gastric retention. These systems are useful to several problems encountered during the development of a pharmaceutical dosage form. In recent years scientific and technological advancements have been made in the research and development of rate-controlled oral drug delivery systems by overcoming physiological adversities, such as short gastric residence times (GRT) and unpredictable gastric emptying times (GET). Systems which are retained in the stomach for a longer period of time and thereby improve the bioavailability of drugs. Several approaches are currently utilized in the prolongation of the GRT, including floating drug delivery systems (FDDS), also known as hydrodynamically balanced systems (HBS), swelling and expanding systems, polymeric bioadhesive systems, modified-shape systems, high-density systems, and other delayed gastric emptying devices. In this review, current & recent developments of Stomach Specific FDDS are discussed. Keywords: Floating Drug Delivery System, Floating Systems, Effervescent Systems, Non-Effervescent Systems.